2013
DOI: 10.18433/j36890
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Terpenes on the Skin Permeation of Lomerizine Dihydrochloride

Abstract: -Purpose. Lomerizine dihydrochloride (LOM) is a Ca2+ channel blocker used as an antimigraine drug, which is currently administered orally in Japan. We therefore investigated the effect of terpenes in propylene glycol (PG) solvent on the percutaneous absorption of LOM by hairless mouse skin. Methods. Attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR), confocal laser scanning microscopy (CLSM), and small angle X-ray scattering (SAXS) were carried out to analyze the effects of terpene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…The shift to a higher frequency occurs when methylene groups of the SC lipid alkyl chains change from trans to gauche conformation, suggesting that the SC lipid is disturbed. The magnitude of blue shift in the peak frequency of the asymmetric and symmetric stretching vibration absorbance is correlated with an increased number of gauche conformers in the lipid acyl chain (Furuishi et al 2013). The areas of these two peaks are in proportional to the amount of the lipids present in SC.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…The shift to a higher frequency occurs when methylene groups of the SC lipid alkyl chains change from trans to gauche conformation, suggesting that the SC lipid is disturbed. The magnitude of blue shift in the peak frequency of the asymmetric and symmetric stretching vibration absorbance is correlated with an increased number of gauche conformers in the lipid acyl chain (Furuishi et al 2013). The areas of these two peaks are in proportional to the amount of the lipids present in SC.…”
Section: Discussionmentioning
confidence: 95%
“…These bands can be attributed to the methylene groups of the SC lipid alkyl chains. It has been demonstrated that PEs which cause a shift to a higher CH 2 stretching frequency improve drug permeation (Casiraghi et al 2010;Furuishi et al 2013). And the decrease of peak area for both CH symmetric and asymmetric stretching absorbance frequency peak caused by PEs also indicated a disruption of the intercellular lipid bilayers (Vaddi et al 2002;Casiraghi et al 2010;Lan et al 2014a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations